Lumberjanes : Friendship to the Max, vol. 2 - Stevenson, Noelle; Ellis, Grace; Allen, Brooke A.; Watters, Shannon; Laiho, Maarta; Aiese, Aubrey (2015)
Five girls become instant best friends when they go to camp and discover there is a lot more to the summer than learning to how to paddle a canoe. Miss Qiunzella Thiskwin Penniquiqul Thistle Crumpet's Camp for Hardcore Lady Types is not your average summer camp and Jo, April, Mal, Molly, and Ripley are not your average campers. Between the river monsters, magic, and myths, this summer is only just beginning!
Volume 1 "Originally published in single magazine form as LUMBERJANES No. 1-4" ; Volume 2 "Originally published in single magazine form as LUMBERJANES No. 5-8" ; Volume 3 "Originally published in single magazine form as LUMBERJANES No. 9-12" ; Volume 4 "Originally published in single magazine form as LUMBERJANES No. 13-16" ; Volume 5 "Originally published in single magazine form as LUMBERJANES No. 17-20"--Copyright page.
Keywords: Teenage girls -- Comic books, strips, etc; Camps -- Comic books, strips, etc; Monsters -- Comic books, strips, etc; Comic books, strips, etc. -- United States; Teenage girls -- Fiction; Camps -- Fiction; Monsters -- Fiction; Cartoons and comics